2022
DOI: 10.1038/s41408-022-00628-2
|View full text |Cite|
|
Sign up to set email alerts
|

Preclinical studies of Flonoltinib Maleate, a novel JAK2/FLT3 inhibitor, in treatment of JAK2V617F-induced myeloproliferative neoplasms

Abstract: Janus kinase 2 (JAK2) hyperactivation by JAK2V617F mutation leads to myeloproliferative neoplasms (MPNs) and targeting JAK2 could serve as a promising therapeutic strategy for MPNs. Here, we report that Flonoltinib Maleate (FM), a selective JAK2/FLT3 inhibitor, shows high selectivity for JAK2 over the JAK family. Surface plasmon resonance assays verified that FM had a stronger affinity for the pseudokinase domain JH2 than JH1 of JAK2 and had an inhibitory effect on JAK2 JH2V617F. The cocrystal structure confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Based on studies, JAK2 V617F mutation was seen in 95% of PV patients and about 50-60% of ET and PMF patients (12,(17)(18)(19). In this study, it was shown that the frequency of JAK2 V617F mutation was 97.1% in PV patients, 50% in ET patients, and 60.25%in PMF patients.…”
Section: Discussionmentioning
confidence: 49%
“…Based on studies, JAK2 V617F mutation was seen in 95% of PV patients and about 50-60% of ET and PMF patients (12,(17)(18)(19). In this study, it was shown that the frequency of JAK2 V617F mutation was 97.1% in PV patients, 50% in ET patients, and 60.25%in PMF patients.…”
Section: Discussionmentioning
confidence: 49%
“…protein domains have been predicted as frequently mutated domains and reported in the DCMP database. Protein Domain Target Function Reference BCL-2* Anti-apoptotic protein Apoptosis [ 191 ] CDK4/6 Cyclin-dependent kinases Cell cycle regulation [ 192 ] EGFR Epidermal growth factor receptor Cell proliferation, angiogenesis [ 193 ] FLT3* FMS-like tyrosine kinase 3 Cell survival, proliferation [ 194 ] HER2 Human epidermal growth factor receptor 2 Cell proliferation, survival [ 195 ] IDH1 Isocitrate dehydrogenase 1 Metabolic reprogramming [ 196 ] JAK2 Janus kinase 2 Cell proliferation, differentiation [ 197 ] KRAS Kirsten rat sarcoma viral oncogene homolog Cell proliferation, survival [ 198 ] mTOR Mammalian target of rapamycin Cell growth, metabolism [ 199 ] NTRK Neurotrophic tyrosine receptor kinase Cell survival, differentiation [ 200 ] PD-L1 Programmed death-ligand 1 …”
Section: Mechanisms Underlying the Impact Of Protein Domain Mutations...mentioning
confidence: 99%